2007
DOI: 10.1115/1.2744430
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Strain Rate on the Dynamic Hardness in Metals

Abstract: Traditionally, the hardness of materials is determined from indentation tests at low loading rates (static). However, considerably less work has been conducted in studying the dynamic hardness of materials using relatively high loading rates. In the present work, two models are used to predict strain rate dependency in hardness. The first model is a power law expression that is based on the dependence of the yield stress on the strain rate. This model is relatively simple in implementation, and it is quite eas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
28
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 18 publications
4
28
0
1
Order By: Relevance
“…Considering the special case n = 2 as proposed in references [24,25], it was found that the best fit for h m was obtained when the impact C 1 was much less than the C 1 ind as listed in This contradicts the general understanding that the dynamic resistance of metals is higher than that obtained under quasi-static conditions [49]. For example, Almasri et al [52][53][54] investigated the strain rate dependence of the dynamic hardness of fcc copper and bcc steel finding that the hardness increased with the increase of the strain rate from 10 -5 to 10 5 s -1 . Moreover, Clough et al [55] studied the dynamic hardness using a dropped ball on steels and found the hardness increased with strain rate up to 10 6 s -1 .…”
Section: Indentation Phasementioning
confidence: 93%
“…Considering the special case n = 2 as proposed in references [24,25], it was found that the best fit for h m was obtained when the impact C 1 was much less than the C 1 ind as listed in This contradicts the general understanding that the dynamic resistance of metals is higher than that obtained under quasi-static conditions [49]. For example, Almasri et al [52][53][54] investigated the strain rate dependence of the dynamic hardness of fcc copper and bcc steel finding that the hardness increased with the increase of the strain rate from 10 -5 to 10 5 s -1 . Moreover, Clough et al [55] studied the dynamic hardness using a dropped ball on steels and found the hardness increased with strain rate up to 10 6 s -1 .…”
Section: Indentation Phasementioning
confidence: 93%
“…Almasri and Voyiadjis [25] developed a physically based temperature and strain rate-dependent expression for microhardness H 0 such that…”
Section: Determination Of the Materials Length Scale And The Hardeningmentioning
confidence: 99%
“…Тестирование осу-ществлялось двумя основными модами нагружения: a) традиционной квазистатической без добавления ос-цилляции, b) посредством метода CSM с наложением дополнительной осцилляции смещения индентора ам-плитудой z = 0.5−8 nm и частотой 45 Hz. Во время проведения всех экспериментов скорость относительной квазистатической деформации поддерживалась постоян-ной (ε = 0.05 s −1 ) с помощью цепей обратной связи в приборе, что позволяло исключить влияние скоростного фактора на величину твердости [33]. Максимальная глубина отпечатков в контрольных образцах (для ко-торых z = 0), устанавливаемая протоколом испытания, составляла 25, 50, 100, 200, 500, 1000, 1500 и 2000 nm.…”
Section: аппаратура материалы и подготовка образцовunclassified